Effect of foliar Application of Yeast Extract & EM-1 Bio-Fertilizer on Fruit Quality and Yeild of Persimmon (Diospyros kaki L.) cv. "Hachyia" (Journal of Hama University, 2019)
Foliar application was used by Yeast extract with two concentrations (4,8 g/L) and  EM-1 with  two  concentrations (3,4 ml/L)  one month pre-harvest  fruits during  season 2017 and its effect on fruit quality and yeild of persimmon cv. Hachyia.The results showed that the yield of yeast foliar application with concentration (8 g / L)  was higher with significant differences in  fruit  weight which reach to (225 gr) compared with the control (173.5 gr). A significant increase in productivity was observed in yeast extract  treatment at concentration (8 g/L)(126.7 kg / tree) while the control was (76.8 kg / tree).In addition, foliar spray with yeast extract  (8 g / L) and  bio-fertilizer treatments (3 , 4 ml / L) significantly increased the total soluble solids rato compard with the control , While vitamin C was increased  by using  yeast extract treatmnet with concentration  (4 gr /L)   and bio-fertilizer with concentration  (3 ml / L) which reach  to (68.57 , 65.17 mg / 100 gr fresh weight) recpectively compared with the control (35.15 mg / 100 gr fresh weight), However  no differences were observed between the treatments in the ratio of reducing sugars and acidity.